2015
DOI: 10.1021/acs.macromol.5b01717
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determination of the Tandem Repeat Motif in Samia cynthia ricini Liquid Silk by Solution NMR

Abstract: The wild silkworm Samia cynthia ricini produces silk fibroin containing polyalanine sequences. The structure of a typical tandem repeat sequence YGGDGG(A) 12 GGAG within S. c. ricini silk fibroin in liquid silk was determined by solution NMR. 13 C, 15 N, and 1 H shifts were assigned from solution NMR spectra for the tandem repeat. TALOS-N was then used to predict the backbone dihedral angles from the chemical shifts. Dihedral angles revealed a well-structured α-helix for the polyalanine region and less stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The native silk fiber was β -sheet-rich whereas the LF aq as-cast film was α -helix-rich. These results are consistent with previous work [12,22], since S. c. ricini LF is known to have a well-structured α -helical conformation in the PA region [27]. This result was well supported by FTIR as shown in the typically α -helix-rich FTIR spectrum of the LF aq as-cast film in Figure 2.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The native silk fiber was β -sheet-rich whereas the LF aq as-cast film was α -helix-rich. These results are consistent with previous work [12,22], since S. c. ricini LF is known to have a well-structured α -helical conformation in the PA region [27]. This result was well supported by FTIR as shown in the typically α -helix-rich FTIR spectrum of the LF aq as-cast film in Figure 2.…”
Section: Resultssupporting
confidence: 92%
“…Similar to the PA sequences in S. c. ricini and other native wild SF, X-ray diffraction, and infrared, Raman and solid-state NMR spectroscopy studies [15,16,17,18,19,20,21,22,23,24] have shown the (GAGAGS) n repeat sequence regions in B. mori silk SF to primarily contribute to the formation of β -sheets [17,19,20,21,25,26]. In addition, the two kinds of SF have other structures such as α -helix and random coil [21,27].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the longer polyalanine region in E. australis repetitive domain leads to the formation of helical structure 55 . The helical structure of the polyalanine in E. australis is also similar to the helical structure of a long polyalanine region (10–14 alanine residues) in Samia cynthia ricini 56 . In the case of E. australis spidroins, hydrophobicity of the repetitive domain and hydrophilicity of the C-terminal domain cause to form micelle-like structure 42 .…”
Section: Discussionmentioning
confidence: 55%
“…There are mainly two kinds of Ala residues in the liquid silk of S. c. ricini stored in the middle silk glands, i.e., Ala residues in the polyalanine sequences (A) n (n = 12, 13) and the isolated Ala residue [ 41 ]. The polyalanine sequences take α-helical conformation, whereas the isolated Ala residues take random coil in the liquid silk [ 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 ]. Therefore, the chemical shifts of the Ala main peaks of S. c. ricini liquid silk are a good chemical shift reference for α-helix, and the small peaks are a good chemical shift reference for the random coil.…”
Section: Structure Of Silk Stored In the Middle Silk Gland Of B Mori Silkwormmentioning
confidence: 99%